2002
DOI: 10.1177/15648265020233s133
|View full text |Cite
|
Sign up to set email alerts
|

Stable Isotope Aided Evaluation of Community Nutrition Program: Effect of Food Supplementation Schemes on Maternal and Infant Nutritional Status

Abstract: The supplementation program of the community nutrition project (PNC) launched by the Senegalese Government in order to protect the most vulnerable groups (children and women) was evaluated. Using a stable isotope (deuterium), we assessed the effect of the PNC on breastmilk output, mother's body composition, and baby's growth at three months of lactation. Breastmilk triglycerides, lactose, protein, and zinc were also determined. Mothers who were supplemented more than 60 days during pregnancy showed a significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(39 citation statements)
references
References 14 publications
(18 reference statements)
1
38
0
Order By: Relevance
“…The effect of maternal energy intake on HM volume has shown conflicting results. Some studies showed that provision of additional calories ( 11 , 128 ), energy restriction ( 12 ), or fasting ( 13 ) had no impact on HM volume, while others showed that a low calorie diet (1,200 kcal per day for 3 days) ( 14 ) or low energy intake ( 15 ) resulted in reduced HM production. In terms of macronutrient composition, an isocaloric high fat diet ( 16 ) and increased dietary consumption of proteins ( 17 ) and carbohydrates ( 18 ) demonstrated an increased HM fat concentrations at different stages.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of maternal energy intake on HM volume has shown conflicting results. Some studies showed that provision of additional calories ( 11 , 128 ), energy restriction ( 12 ), or fasting ( 13 ) had no impact on HM volume, while others showed that a low calorie diet (1,200 kcal per day for 3 days) ( 14 ) or low energy intake ( 15 ) resulted in reduced HM production. In terms of macronutrient composition, an isocaloric high fat diet ( 16 ) and increased dietary consumption of proteins ( 17 ) and carbohydrates ( 18 ) demonstrated an increased HM fat concentrations at different stages.…”
Section: Resultsmentioning
confidence: 99%
“…The data for the analysis are drawn from 12 countries from across 5 continents ( Table 1): Bangladesh (10), Brazil (11,12), Chile (13), Kenya (14), Malawi (15), Mexico (16), Papua New Guinea (PNG) (17), Senegal (18), The Gambia (19), USA (20), UK (21)(22)(23), and Zambia (24). Initially, these data were located through a list of research groups that conducted deuterium oxide measurements of lactation kept in Coward's records and completed with a literature search.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…The standard operating procedure of using DTM has been largely explained by the International Atomic Energy Agency [19] and is detailed in much of the existing literature [8,9,11,12,[20][21][22][23]. Briefly, after pre-dose saliva collection, a 30 g dose of deuterium oxide was administered, and post-dose saliva samples were collected in cryogenic tubes from the mother (~4 ml) and child (~3 ml) pair on the 1st, 2nd, 3rd, 4th, 13th and 14th days after dose administration to the mother.…”
Section: Data Collected Determination Of Exclusive Breastfeeding Pracmentioning
confidence: 99%
“…The evaluation of education and counselling programmes is usually based on maternal report, which is easy and cost effective to obtain but has major limitations. A review of studies conducted in numerous developing countries using the isotope technique to validate mothers' reports has shown that the discrepancy between mothers' recall (24 h) and the deuterium oxide dose-to-mother technique (DTM) can be as high as 40% at 3-6 months of age [8][9][10][11][12]. There is a discrepancy between mothers' recall and DTM because mothers tend to over report their adherence to the practices to gain the approval of the interviewer or underreport because of lapses in memory [13].…”
Section: Introductionmentioning
confidence: 99%